Karakteristik Aerodinamika Pontoon Pesawat NXXX Versi Amfibi - Irsabudi, Andreas Maulana; Jatisukamto, Gaguk; Sutjahjono, Hary (Jurnal Rekayasa Mesin, 2021)
Seaplanes are aircraft that can take off and landing on water. A seaplane’s requirement is its need to take off and landing on watery conditions which is equipped with a pontoon.  Pontoon of a seaplane needs to be evaluated in terms of aerodynamics characteristics when a seaplane flies. The purpose of this study is to determine the correlation of various geometric combinations of deadrise angle, step height, and constant cross-section length with the values of coefficient of drag (CD), coefficient of lift (CL) and coefficient of moment (CM). The methodology was carried out by simulating Computational Fluid Dynamics (CFD) using OpenFOAM software. The results of this study could be concluded that deadrise angle affected coefficient of drag (CD), coefficient of lift (CL) and coefficient of moment (CM) with each value of 0.0055, 0.0044, -0.0036, while step height didn’t influence significantly on coefficient of drag (CD) and didn’t affect coefficient of lift (CL) and coefficient of moment (CM). Constant cross-section length didn’t affect significantly on coefficient of drag (CD) and coefficient of lift (CL) but increasing constant cross-section length increased coefficient of moment (CM) with a value of -0.0039.